The importance of learning context in approaches to learning / Nur Fakhzan Marwan - Marwan, Nur Fakhzan (Universiti Teknologi MARA Cawangan Pahang, 2005)
The way students approach their learning is linked to the quality of their learning outcomes. However, approaches to learning, deep and surface approaches, should not be seen as uniquely a characteristic of the student, but as a response to a situation. Many researchers believe that although the concepts of learning approaches are not applicable to the individual students, it can describe students in particular learning condition. This means that the contextual factors are believed to have greater impacts on students’ approaches to learning. Thus, this paper discusses a framework that explores the variables or contextual factors that affect, hence, influence the adoption of approach to learning, such as students’ interest and experiences, feedback, assessment, teaching, and course structures in academic departments. The framework has some pedagogical implications that could promote quality learning.